Reducing electrical energy consumption through behaviour changes. Issue 1 (28th January 2014) - Kemp-Hesterman, Aaron; Glick, Scott; Eileen Cross, Jennifer
Abstract : Purpose: – The purpose of this paper is to look at the effect of human behaviour, and efforts to change that behaviour, on electricity consumption in a high school setting. Design/methodology/approach: – The study uses a mixed methods design of interviews and historical electrical use data to assess two treatments impacts on electrical consumption over time at two Fort Collins high schools. Findings: – Both treatments, the energy efficiency awareness campaign and the energy efficiency charrette, were found to have a positive impact on decreasing levels of electricity consumption. Unfortunately, these decreases lessened over time. The key attributes of communication, motivation, and leadership were identified as necessary at the high school facilities level to ensure long-term success in decreased electrical consumption. Research limitations/implications: – The implications of this research focus on awareness of energy use in public schools and how to use awareness as a cost-effective tool in decreasing electrical consumption. The limitations are the inability to isolate HVAC consumption loads and the small study size. However, this is one of, if not the first, effort to use awareness campaigns and charrettes in a high school setting to decrease electrical use. Additional research would answer questions like: how to increase the charrette impact time; could these programs be adopted district wide at all grade levels; how could energy awareness be institutionalized so periodic charrettes are not necessary? Limitations include the inability to isolate heating and cooling electricity loads from the data. Originality/value: – This study is the first of its kind and has value to facilities management personnel, custodians, faculty and administration members, particularly in a high school setting. This research provides a framework and potential guidance for a school organization to conserve electrical energy and achieve cost savings and environmental benefits.